2019
DOI: 10.1002/masy.201800008
|View full text |Cite
|
Sign up to set email alerts
|

Titanate Nanotubes Modified With Zinc and Its Application in Post‐Consumer PET Depolymerization

Abstract: The development of nanostructures has received notoriety due to the properties that the nanometric scale provides to the material. Among these properties, the increase in the catalytic activity due to the high specific surface area of nanostructures has been the focus of several studies. Among the nanometric catalysts that have been studied, titanate nanotubes present versatility of applications since they can be modified through the functionalization or ion exchange adding the structure metals that increase t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…The combination of these materials can potentially yield a composite material with improved properties compared to those of individual components. The project also used a general purpose epoxy resin named RG01 and an amine-based hardener called CA01 for binding, as these materials are widely used in the development of advanced composite materials due to their excellent properties, such as high strength, strong adhesion to substrates, excellent electrical insulation, low toxicity, minimal shrinkage, and low cost [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43].…”
Section: Methodsmentioning
confidence: 99%
“…The combination of these materials can potentially yield a composite material with improved properties compared to those of individual components. The project also used a general purpose epoxy resin named RG01 and an amine-based hardener called CA01 for binding, as these materials are widely used in the development of advanced composite materials due to their excellent properties, such as high strength, strong adhesion to substrates, excellent electrical insulation, low toxicity, minimal shrinkage, and low cost [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43].…”
Section: Methodsmentioning
confidence: 99%
“…This group later modified the TNT with sodium (NaTNT) and zinc (ZnTNT) by adopting a facile singlestep hydrothermal method. [85] It was found that the ZnTNT exhibited the highest catalytic activity obtaining BHET yield of 87 % at 196 °C in 3 h (Table 1, entries 16,17).…”
Section: Nanocatalystsmentioning
confidence: 99%
“…They reported 84 % BHET yield in 2 h of virgin PET glycolysis over TNT, which is slightly higher than the commercial zinc acetate catalyst (Table 1, entry 15). This group later modified the TNT with sodium (NaTNT) and zinc (ZnTNT) by adopting a facile single‐step hydrothermal method [85] . It was found that the ZnTNT exhibited the highest catalytic activity obtaining BHET yield of 87 % at 196 °C in 3 h (Table 1, entries 16, 17).…”
Section: Glycolysismentioning
confidence: 99%
“…PETs have excellent mechanical properties, creep resistance, fatigue resistance, friction resistance, and dimensional stability over wide temperature ranges (Table 4) [99,110]. However, the disadvantages of slow crystallization rate, machining difficulties, high molding temperature, and poor impact Hardness (Shore-A) 96 [105] Tan δ at peak (°C) 75-100 [91,108] Tan δ values at peak 0.42 [91] Dielectric constant (1 MHz) 4).…”
Section: Properties Of Petmentioning
confidence: 99%